2016
DOI: 10.1097/md.0000000000004013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 -1082 G/A gene polymorphisms in Egyptian children with CAP

Abstract: Community-acquired pneumonia (CAP) is one of the leading causes of death worldwide. Cytokines are involved in the pathogenesis of CAP. To date, only a few studies concerned the association of interleukin-10 (IL-10) gene polymorphisms with CAP.In this study, we aimed to investigate whether the -1082(G/A) polymorphism in the promoter region of the IL-10 gene is involved in susceptibility to and the outcome of CAP, and we also measured the serum level of IL-10 to assess its relation to such polymorphism.This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Many studies show that the IL10 − 1082 genotypes A/G+G/G were the largest producers of IL-10 ( 23 , 36 38 ). Despite the association of A/G+G/G genotypes with AS and increased levels of IL-10 in patients, we did not find any association between these genotypes and the levels of IL-10, suggesting that other SNPs could influence the production of the cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that the IL10 − 1082 genotypes A/G+G/G were the largest producers of IL-10 ( 23 , 36 38 ). Despite the association of A/G+G/G genotypes with AS and increased levels of IL-10 in patients, we did not find any association between these genotypes and the levels of IL-10, suggesting that other SNPs could influence the production of the cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…55 Also in line with this, a case-control study on pneumonia showed that Egyptian children with GG genotype had increased levels of IL-10. 56 This increased circulatory IL-10 level of individuals with a single copy or double copy of the mutant allele compared to individuals with homozygous ancestral genotype AA in our study suggests that a single copy of the mutant allele G enhances the IL-10 expression. Our findings are in tandem with the earlier reports on influence of -1082G IL-10 (rs1800896) polymorphism on circulatory IL-10 levels.…”
Section: Discussionmentioning
confidence: 45%
“…The majority of these have focused on innate immune molecules, such as toll-like receptors and proinflammatory cytokines. Several associations of pneumonia susceptibility and severity with single nucleotide polymorphisms in the interleukin-6, interleukin-10, toll-like receptors TLR2, TLR4, and TLR9, C-reactive protein (CRP), and nitric oxide synthase 3 (NOS3) genes were reported [187][188][189][190][191]. We have summarized these in Table 5.…”
Section: Genetic Contributions To Pneumonia Risk and Severitymentioning
confidence: 99%